Reaksi Pasar atas Pergantian Nama Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2012–2022 - Gunawan, Dewa Ngakan Putu Hary; Wirama, Dewa Gede (Jurnal Samudra Ekonomi dan Bisnis, 2024)
The aim of research is to analyze market reactions to changes in names of companies listed on the Indonesia Stock Exchange in 2012-2022. The information content of a company name change is tested based on market reactions as proxied by cumulative abnormal returns. The event study approach is used with a window period of seven days with the event date being the date the company decides to change its name at the RUPS/RUPSLB. Sampling of 90 companies was carried out using the purposive sampling method. The hypothesis is tested with a one sample t-test or one sample Wilcoxon signed rank test. The results show that there was a negative market reaction to the change of name of companies listed on the Indonesia Stock Exchange in 2012-2022 on the first to the third day after the announcement of the company name change. This research provides additional empirical information regarding how the market reacts to a company name change.